Pulmonary Tuberculosis Patient with destroyed lung: Case Report - Saragih, David; Upeksha, Anak (Malang Respiratory Journal, 2023)
Tuberculosis is still a concern of WHO because there is an increase in TB cases, especially in Southeast Asia, one of which is Indonesia, which is the second in the world that has not shown a decrease in cases. Where people who have comorbid diseases are more susceptible to tuberculosis. Destroyed lung is a lung damage caused by tuberculosis.